Design and Implementation of a Mobile Tourist Recommendation System for Sleman Using the Haversine Formula - Faizy, Akmal; Sutopo, Joko (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2025)
Tourists often face challenges in accessing relevant information and navigating destinations due to the fragmented nature of existing mobile applications. This study addresses these issues by developing a mobile-based tourist recommendation system tailored to Sleman Regency, Yogyakarta. The system integrates features such as destination recommendations using the Haversine formula for proximity calculations, ticket purchasing, real-time navigation, a curated list of local culinary options, and a bug-reporting mechanism. Developed using the Agile methodology, the system underwent iterative enhancements based on user feedback. User preferences, including travel categories (e.g., nature, culture, family, temple) and culinary interests, are dynamically analyzed to provide personalized recommendations. The culinary feature highlights traditional dishes and popular dining spots, promoting local gastronomy. Black-box testing verified the system’s functionality, achieving a 100% success rate, while feedback mechanisms were incorporated to enable continuous improvement. The system ensures data privacy and security through robust encryption and regulatory compliance. It is scalable and adaptable, with potential applications beyond Sleman Regency. Furthermore, the system promotes sustainable tourism by encouraging eco-friendly destinations, respecting local cultural values, and supporting local culinary businesses. A comparative analysis highlights its advantage over conventional multi-application solutions by consolidating key features into a unified platform. This integrated solution streamlines tourist planning, navigation, and culinary exploration, enhancing convenience, user engagement, and satisfaction while contributing to the growth of Sleman’s tourism sector.